1998
DOI: 10.1039/a801100a
|View full text |Cite
|
Sign up to set email alerts
|

New approach to sequential injection analysis: using the sample as carrier

Abstract: A new way of implementing sequential injection analysis involving the use of the sample as a carrier is proposed. These systems are especially suitable for constructing continuous monitoring set-ups with no restrictions regarding the amount of sample which can be processed. A new standard addition methodology was used to calibrate the proposed system. The methodology was applied to the determination of Fe II with ophenanthroline (a reaction which involves a single reagent) and that of phosphorus by formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Especially prominent among the early software used with flow techniques was Flowtek, which was developed by van Staden and coworkers [1]; FIALab, which was devised by Ruzicka's group [2]; and DARRAY [3], which was developed by our research group. Some of these computer programs continue to be readily available and used at present as they greatly facilitate the implementation of flow techniques.…”
Section: Software For Flow Techniquesmentioning
confidence: 99%
“…Especially prominent among the early software used with flow techniques was Flowtek, which was developed by van Staden and coworkers [1]; FIALab, which was devised by Ruzicka's group [2]; and DARRAY [3], which was developed by our research group. Some of these computer programs continue to be readily available and used at present as they greatly facilitate the implementation of flow techniques.…”
Section: Software For Flow Techniquesmentioning
confidence: 99%
“…Among these, iron is the most determined metal in waters, if the two possible ionic forms are considered [49,59,71,74,83,103,127,[135][136][137]143,144,152]. This fact can be explained as iron determination can be fairly easy to obtain with spectrophotometric detection, due to well-known reactions.…”
Section: Changes In Oxidation Statementioning
confidence: 99%
“…That was the case of the work developed by Makchit et al [71]; the authors designed a homemade sequential injection system providing valuable information for "a do it yourself SI manifold". Other examples are described by Vieira et al [137] and Mas et al [135], involving different strategies of sampling and the use of sample as carrier stream.…”
Section: Changes In Oxidation Statementioning
confidence: 99%
See 1 more Smart Citation
“…Mas et al 186 demonstrated that the sample could be employed as the carrier stream, thus facilitating the use of inline standard additions for the successful determination of iron(II) and phosphorus in spiked waters. The only drawback with this idea was that the syringe pump required rinsing after each change of sample to avoid memory effects.…”
Section: Ultraviolet and Visible Absorbancementioning
confidence: 99%